PENERAPAN METODE CROUSE REVIEW HORAY (CRH) DALAM UPAYA PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - Siti Maryam; Evan Farhan Wahyu Puadi; Abdul Rosyid (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
This research was motivated by the importance of understanding students' mathematical abilities in mathematics. The ability of mathematical understanding is one of the most important goals in the attainment of the objectives of the learning of mathematics. Metematis understanding is also an early ability students need to have in order to improve other capabilities in order to achieve educational goals. But the fact metematis student comprehension ability is still very low. This can be seen when the researchers conducted interviews with a teacher of mathematics courses at MTs Negeri Kadugede stating that the resulting value in each exam students are still a lot below average values. It is caused by several factors which include instructional methods used by teachers when teaching. In this study, researchers used a method Course Review Horay (CRH) in each of the learning process. The purpose of this study was to determine whether there is an increased understanding of mathematical ability of students to use methods Course Review Horay (CRH). The research was conducted in classes VII B to the experimental class and class C to class VII MTs Kadugede control in the second semester of the school year 2015-2016. The method of the research used experimental method. Data collection techniques in this study using the test, the student response sheet. The validity of the instrument is checked by means tested. The test was tested with validity, reliability, level of difficulty, and distinguishing features. The data were analyzed descriptively and quantitatively. The analysis technique used is the t-test to test similarity Two average to see that the two classes, namely the experimental class and the control class are in the same circumstances, the t-test for Test Difference Two average to examine the differences between the two classes, a class experiment and a control class that are in different circumstances and test the one hand to determine the increase of the experimental class. Through the experimental method initial test results obtained with the average value of 21.395 experimental class and the average value of 20.5 grade control. While at the end of the test values obtained average grade class experimental and control 76.42 35.81. From the analysis of the initial data and the final data sample can be concluded that the study of mathematics by using method Course Review Horay (CRH) is better than direct instruction to improve mathematical understanding in Kadugede MTs. Besides from analysis of student response sheet reveals the response of students to the study of mathematics by Course Review Horay (CRH) is quite good